PENGARUH INVESTASI LUAR NEGERI, PENDIDIKAN DAN TEKNOLOGI INFORMASI-KOMUNIKASI TERHADAP TINGKAT PARTISIPASI ANGKATAN KERJA DI INDONESIA - Cherrly Wahyuni; Ali Anis (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This research aims toαexamined theαeffectαof foreign investment, education and information-communication technologhy on labor force participation rate in Indonesia with the selected model is the fixed effect model (FEM). Theαdata αused isαpanelαdataαduringαtheαperiod 2013-2017, with tewchnique of collecting documentation data and library studies obtained fromm relevant institution and agencies.The variables use are labor force participation rate, foreign invesment, education and information-communication technologhy . the research method used is Ordinary Least Square (OLS). The estimation result show that, foreign investment have a positive and its  significant effect on labor force participation rate in Indonesia. Education have a neegative and significannt effect on labor forcce participation rate in Indonesia. Information- communication technologhy have a negative and its  significant  effect on labor force participation rate in Indonesia. Meanwhile simultaneously foreign invesmnet, education and information-communication technologhy affect the labor force participation rate in Indonesia.